Comparative effects of graphene oxide and sodium alginate on filter paper against S. aureus and E. coli - Choopan, Wachiraporn; Kittiamornkul, Navapadol (Creative Science, 2025)
This research investigated the efficacy of graphene oxide (GO) and sodium alginate (SA) solutions in inhibiting the growth of Staphylococcus aureus and Escherichia coli bacteria coated on filter papers. The study compared the antibacterial properties of GO solution alone, GO mixed with SA at different ratios, and a control group. In the experiment, S. aureus and E. coli bacteria were cultured. The coated filter papers were soaked in the aforementioned bacteria and dried in a sterile cabinet. Finally, the dilutions were performed, sequentially. The results show that filter paper coated with 1% GO solution gave the best antibacterial activity against E. coli which had 45.79% reduction, but it did not significantly better than the paper coated with GO mixed with SA (ratio 1:1) which had 45.02% reduction. All coated paper samples had low antibacterial activity against S. aureus significantly (p-value < 0.05). GO solution normally lacks adhesion properties but mixing it with SA provided adhesion while maintaining antibacterial activity. This research can be applied to antimicrobial paper, textile industries, prosthesis organs and canvas printing. Further research is needed to explore human applications’ long-term effectiveness and safety. GRAPHICAL ABSTRACT HIGHLIGHTS The synergistic effects of graphene oxide and sodium alginate coating on filter paper against aureus and E. coli The mixture of graphene oxide and sodium alginate (ratio 1 : 1) showed the best antibacterial activity against Escherichia coli This research can apply to antimicrobial paper, textile industries, prosthesis organ and canvas printing